Stabilization of Lithium-Metal Batteries Based on the in Situ Formation of a Stable Solid Electrolyte Interphase Layer - Park, Seong-Jin; Hwang, Jang-Yeon; Yoon, Chong S.; Jung, Hun-Gi; Sun, Yang-Kook (American Chemical Society, 2018)
Lithium (Li) metals have been considered most promising candidates as an anode to increase the energy density of Li-ion batteries because of their ultrahigh specific capacity (3860 mA h g(-1)) and lowest redox potential (-3.040 V vs standard hydrogen electrode). However, unstable dendritic electrodeposition, low Coulombic efficiency, and infinite volume changes severely hinder their practical uses. Herein, we report that ethyl methyl carbonate (EMC)- and fluoroethylene carbonate (FEC)-based electrolytes significantly enhance the energy density and cycling stability of Li-metal batteries (LMBs). In LMBs, using commercialized Ni-rich Li[Ni0.6Co0.2Mn0.2]O-2 (NCM622) and 1 M LiPF6 in EMC/FEC = 3:1 electrolyte exhibits a high initial capacity of 1.8 mA h cm(-2) with superior cycling stability and high Coulombic efficiency above 99.8% for 500 cycles while delivering a unprecedented energy density. The present work also highlights a significant improvement in scaled-up pouch-type Li/NCM622 cells. Moreover, the postmortem characterization of the cycled cathodes, separators, and Li-metal anodes collected from the pouch-type Li/NCM622 cells helped identifying the improvement or degradation mechanisms behind the observed electrochemical cycling.
Keywords: FLUOROETHYLENE CARBONATE; ELECTROCHEMICAL PROPERTIES; ION BATTERIES; LI; ANODE; POLYSULFIDE; DEPOSITION; CATHODES; SOLVENT